THE INFLUENCE OF LOOSE PART MEDIA ON THE ABILITY TO RECOGNIZE LETTERS IN CHILDREN AGED 4-5 YEARS - Aerin, Wafa; Risdianto Hermawan; Aprilia Wahyuning Fitri; Ardila Laeli Isnaeni (JOYCED: Journal of Early Childhood Education, 2025)
This research aims to determine the effect of loose part media on the ability to recognize letters in children aged 4-5 years at Pertiwi Kindergarten 14.07.08 Mekarsari Village. This research was motivated by the ability to recognize letters in children aged 4-5 years at Pertiwi Kindergarten 14.07.08 Mekarsari Village which still needs improvement. This research is experimental research with a pre-experimental design carried out in pre-test, treatment and post-test stages. The data collection methods used in this research are observation and documentation, while the data analysis techniques used are validity, reliability and normality tests. The results of the study showed that the ability to recognize letters in children aged 4-5 years had changed after treatment. Thorough recognition of letters using loose part media has an influence on the ability to recognize letters in children aged 4-5 years at Pertiwi Kindergarten 14.07.08 Mekarsari Village. Children's ability to recognize letters during the pre-test shows that they still need improvement. Next, the child or respondent is given treatment using loose part media for 2 times, then the child is observed again using a post-test to find out the difference between the pre-test and the results after the treatment. The results of the post-test show a better change in the ability to recognize letters in children aged 4-5 years, which means that the use of loose part media has an effect on the ability to recognize letters in children aged 4-5 years.